2021
DOI: 10.1016/j.clinthera.2021.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Effectiveness of Once-Weekly Semaglutide From a US Commercially Insured and Medicare Advantage Population

Abstract: Purpose: Patients managing type 2 diabetes mellitus (T2DM) often require combination therapy to meet their blood glucose control targets. With limited realworld evidence focused on the use of glucagon-like peptide 1 receptor agonist (GLP-1RA) therapies, the objective of this study was to describe the association between semaglutide once weekly (OW) initiation and changes in hemoglobin A 1c (A 1c ) levels.Methods: This retrospective, descriptive cohort study used the HealthCore Integrated Research Environment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
6
11
0
Order By: Relevance
“…It should also be acknowledged that the 1.0 mg dose was prescribed to only 22% of cases, implying that up-titration was incomplete in most cases possibly due to the choice of clinicians, concomitant therapies of the population sample, and underlying intentions to limit occurrence of side effects. Nevertheless, the effect of treatment on HbA1c and weight was similar to that reported in most RWE studies [ 24 31 ]. Points of potential strength of the study are constituted by the wide characterization of our cohort including 102 different variables and the broad representativeness of our patient population.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…It should also be acknowledged that the 1.0 mg dose was prescribed to only 22% of cases, implying that up-titration was incomplete in most cases possibly due to the choice of clinicians, concomitant therapies of the population sample, and underlying intentions to limit occurrence of side effects. Nevertheless, the effect of treatment on HbA1c and weight was similar to that reported in most RWE studies [ 24 31 ]. Points of potential strength of the study are constituted by the wide characterization of our cohort including 102 different variables and the broad representativeness of our patient population.…”
Section: Discussionsupporting
confidence: 85%
“…RWE studies on GLP-1RAs have provided extensive evidence that OW semaglutide reduces HbA1c and body weight irrespective of previous GLP-1 RA use, with potentially higher persistence than other GLP-1 RAs [ 24 43 ]. Our results show that OW semaglutide induced significant reduction in mean HbA1c independent of age, gender, insulin therapy, prior history of GLP-1RA use and diabetic complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the US, the EXPERT study based on the use of EMRs showed that switching to injectable semaglutide from any other GLP-1RA was associated with significant improvements in HbA1c ( N = 710) at 6 months (− 0.7%) and sustained at 12 months; weight reductions ( N = 921) were also significant at 6 months (− 2.1 kg) and greater at 12 months (− 2.8 kg) [ 26 ]. In addition, data from the US Commercially Insured and Medicare Advantage Population ( N = 1888) showed that naïve patients obtained a reduction in HbA1c two times larger than that of switchers (− 1.2% vs. 0.6%); additionally, among the subgroup of patients with a baseline HbA1c value > 9% (75 mmol/mol), percentage point changes in HbA1c were − 2.2% (− 24.0 mmol/mol) [ 27 ]. Another US retrospective study using Optum's de-identified Clinformatics® Data Mart Database assessed that persistence at 360 days was significantly greater with semaglutide (67%) than for comparators (dulaglutide 56%, liraglutide 40%, and exenatide QW 35.5%), while adherence was comparable or greater [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are broadly comparable with those from existing real-world evidence and RCTs. [1][2][3]5,[7][8][9][10] However, the mean weight and HbA1c in our study were greater than those of RCT cohorts, reflecting current UK practice in management of type 2 diabetes that prioritizes GLP-1RA use for people who are probable to benefit from significant weight loss. We were not able to assess the relative effectiveness of semaglutide doses above 1.0 mg once weekly, nor of oral semaglutide, nor doses of dulaglutide above 1.5 mg once weekly, because these were not licensed at the time of data collection.…”
Section: Discussionmentioning
confidence: 57%